2005
DOI: 10.1037/0278-7393.31.6.1502
|View full text |Cite
|
Sign up to set email alerts
|

Testing the multiple in the multiple read-out model of visual word recognition.

Abstract: This study provided a test of the multiple criteria concept used for lexical decision, as implemented in J. Grainger and A. M. Jacobs's (1996) multiple read-out model. This account predicts more inhibition (or less facilitation) from a masked neighbor when accuracy is stressed more but more facilitation (or less inhibition) when the speed of responding is emphasized more. The authors tested these predictions by stressing accuracy (Experiment 1) and response speed (Experiment 2). The results of Experiment 1 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…These contrasting priming effects due to prime lexi-cality are analogous to the results reported in previous masked priming studies using English words (e.g., Davis & Lupker, 2006) and are most consistent with the conclusion that lexical competition plays a role in the processing of Kanji words. Our results also nicely converge with those of De Moor et al (2005), who found that lexical decision instructions that stressed accuracy over speed produced a larger inhibitory neighbor priming effect.…”
Section: Discussionsupporting
confidence: 90%
“…These contrasting priming effects due to prime lexi-cality are analogous to the results reported in previous masked priming studies using English words (e.g., Davis & Lupker, 2006) and are most consistent with the conclusion that lexical competition plays a role in the processing of Kanji words. Our results also nicely converge with those of De Moor et al (2005), who found that lexical decision instructions that stressed accuracy over speed produced a larger inhibitory neighbor priming effect.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore it is possible that participants devised strategies to deal with similar primes and targets (Neely, 1991). A word prime in the similar condition might bias participants in favor of a word decision, for example, by increasing the global evidence for a word (De Moor, Verguts, & Brysbaert, 2005;Grainger & Jacobs, 1996). However, such a bias would produce a priming facilitation.…”
Section: Word Primes and Targets: Strategic Influences Biases And Armentioning
confidence: 86%
“…Using this technique, Segui and Grainger (1990) observed longer RTs for targets that were preceded by a higher frequency neighbor (e.g., "avec-AVEU" [with-confession], with the word "avec" being more frequent in French), compared to targets that followed a higher frequency word that had no letters in common with the target (e.g., "puis-AVEU" [then-confession]). Several later studies have corroborated this effect (e.g., Bijeljac-Babic, Biardeau, Brysbaert, Lange, & Van Wijnendaele 2000;Davis & Lupker, 2006;De Moor, Verguts, & Brysbaert, 2005). Recently, De Moor and Verguts (2006) showed that this effect is also observed when primes and targets are of the same high frequency.…”
mentioning
confidence: 78%